On the acoustic attenuation characteristics of sonar detection in the salt-cavern gas storage environment - Yang, Haiyan; Wang, Yu; Dai, Yao; Zhang, Junfu; Chen, Gang (Frontiers in Earth Science, 2023)
Aiming at the acoustic attenuation in the salt-cavern environment, this paper established a theoretical relationship of the ultrasonic attenuation in the salt-cavern gas storage, based on the wave equation of the acoustic wave propagating in a non-ideal medium, and considering the specific environment of gas storage, and analyzes how the wall roughness of the gas storage affects the acoustic attenuation. The results show that the inner wall roughness of the salt-cavern gas storage has an effect on the acoustic attenuation. The inner wall surface is at the solid-liquid interface, where the change of the medium will affect the attenuation of the acoustic wave, and the effective reflection coefficient of the inner wall will cause the acoustic wave to attenuate at a lower frequency. On this basis, the characteristics of insoluble particles in the salt-cavern gas storage were also studied, and the main components of different media in salt-cavern cavities and the diameter distribution of different particles were obtained, and an experimental platform was established. According to the experimental results, the roughness of a reflective surface significantly affects the attenuation coefficient of the acoustic wave, and the acoustic wave will suffer two energy losses on a rough wall surface. In addition, the insoluble particles also affect the acoustic attenuation significantly, and scattering attenuation increases with the particle size. The research conclusions provide theoretical basis for the variation characteristics of ultrasonic attenuation with the environmental medium and ultrasonic excitation frequency of the salt-cavern gas storage.